Portugal nutritional transition during the last 4 decades: 1974–2011 - Bento, Alexandra (2018)
Objective: To examine trends in food availability for Portugal during the last 4 decades (1974–2011) and analyze such changes in accordance with the nutritional transition theory.Methods: Food balance sheets from Portugal from 1974 to 2011 were analyzed for potential trends by linear regression to study the availability of protein, fat, carbohydrate, ethanol, and total energy and the availability of the following food groups: (i) cereals and tubers; (ii) vegetables; (iii) fruit; (iv) milk; (v) meat, fish, and eggs; (vi) fat; (vii) pulses; (viii) alcoholic beverages; and (ix) sugar and sweeteners. A comparison regarding protein, fat, and carbohydrate availability and WHO recommendation was also performed.Results: The data suggest that in Portugal food availability and consumption have changed throughout the analyzed period. The national availability of most food groups increased considerably, which also resulted in an increase in daily energy. The consumption of cereals and tubers, pulses, and alcohol diminished during this time. Energy availability increased by 406 kcal/person/day, a result from an increase in protein and fat. Protein availability was in accordance with WHO recommendations during the 4 decades analyzed, whereas carbohydrate have always been below the recommended level and fat has been above the recommended level since the second decade (1984).Conclusion: Portugal has crossed into a nutritional transition over the last 4 decades, revealing characteristics of a pattern of degenerative diseases. The country may experience a new nutritional transition that would involve positive changes of behavior, as observed in other developed countries, driven by community multisectorial strategies.